If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(-8m + -6) = -6m + -22 Reorder the terms: -8(-6 + -8m) = -6m + -22 (-6 * -8 + -8m * -8) = -6m + -22 (48 + 64m) = -6m + -22 Reorder the terms: 48 + 64m = -22 + -6m Solving 48 + 64m = -22 + -6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6m' to each side of the equation. 48 + 64m + 6m = -22 + -6m + 6m Combine like terms: 64m + 6m = 70m 48 + 70m = -22 + -6m + 6m Combine like terms: -6m + 6m = 0 48 + 70m = -22 + 0 48 + 70m = -22 Add '-48' to each side of the equation. 48 + -48 + 70m = -22 + -48 Combine like terms: 48 + -48 = 0 0 + 70m = -22 + -48 70m = -22 + -48 Combine like terms: -22 + -48 = -70 70m = -70 Divide each side by '70'. m = -1 Simplifying m = -1
| 4v-2=-10 | | 1920*x=195 | | 18(1-a)= | | 134=14c | | 2(q+2)=8 | | 3/4=Y/7 | | 1080*x=917 | | 1080-x=163 | | -24=-12w | | -7=3v+2 | | 24=-w/6 | | 4z/7-5=-2 | | 144+12c=300 | | 2*2*2+-3*-3= | | 1080*x=955 | | -u/6=-42 | | 20=2+3u | | (7x^4)/(sqrt(2x-8)) | | 2.3log(x)=3log(6-x) | | 6x+y+z=10 | | -4u+5=5-4u | | 1920*x=5 | | -15=4u-3 | | 4lnx-1=6 | | 5/4=7x^2-x | | 42+x=(13+x)*2 | | 21y+7=5 | | 5/2*32 | | Y=-xy-3x-3 | | 11=2/3x-3 | | 2y=5y-8 | | 1920*x=2 |